De-Risking by Banks in Emerging Markets : Effects and Responses for Trade - Starnes, Susan; Kurdyla, Michael; Alexander, Alex J. (International Finance Corporation, Washington, DC, 2018)
Emerging evidence suggests that de-risking is a reality. Increased capital requirements, coupled with rising Know-Your-Customer, Anti-Money-Laundering, and Combating-the-Financing-of-Terrorism compliance costs have resulted in the exit of several global banks from cross-border relationships with many emerging market clients and markets, particularly in the correspondent banking business. A subset of this business, trade finance, is also at risk, with potential consequences for segments of emerging market trade. The emerging market trade finance gap was significant before the crisis and has since likely expanded. Those involved in addressing the de-risking challenge must focus on compliance consistency and effective adaptation of technological innovations.